Influence of annealing on anisotropic crystalline structure of HDPE cast films - Ali Yadegari; Jalil Morshedian; Hossein-Ali Khonakdar; Udo Wagenknecht (Polyolefins Journal, 2016)
High density polyethylene (HDPE) films were produced using cast film extrusion process with different draw ratios, ranging from 16.9 to 148.8. Morphology, crystallinty and orientation state of crystalline and amorphous phases of the cast films were investigated using scanning electron microscopy (SEM), differential scanning calorimetry (DSC) and polarized Fourier transform infrared spectroscopy (FTIR) analyses, respectively. The anisotropic crystalline structures of row-nucleated lamellar morphology were observed for the films produced with high draw ratios. The crystalline phase axes orientation functions were found to be significantly dependent on the applied draw ratios. As expected, annealing increased the crystallinity and melting point temperature (Tm) of the cast films and on the other hand, it also enhanced the crystalline phase orientation. However, the results revealed that annealing also promoted non-twisted lamellar structures, since it increased fc values (c-axis orientation function) and decreased fa values (a-axis orientation function) simultaneously. Additionally, it was found that the annealing induced enhancement in c-axis orientation function was more significant for the cast films with lower draw ratios, therefore, it was dependent on the draw ratio.